Hubungan Dukungan Iman Orang Tua dan Dukungan Iman Pembina Remaja Terhadap Spiritualitas Remaja - Kristi, Sara Kurnia; Suhendra, Junianawaty (Sekolah Tinggi Teologi Tawangmangu, 2025)
Faith support plays an important role in shaping adolescent spirituality. Adolescents who receive simultaneous faith support from parents and youth mentors tend to have higher levels of spirituality. This study aims to determine the relationship between parental faith support and youth mentors' faith support on adolescent spirituality. This study uses a quantitative method with data collection techniques through distributing questionnaires. The subjects of the study consisted of 120 adolescents aged 15–25 years who were active in the Jakarta Christian Church. The sampling technique used purposive sampling, while data analysis was carried out using the Pearson Product Moment correlation test. The results of the study showed a significant relationship between parental faith support and youth mentors' faith support on adolescent spirituality. The faith support provided synergistically by both parties showed a significant positive correlation with the development of adolescent spirituality. These findings provide an important contribution to adolescent development, by emphasizing the need for collaboration between youth mentors in the church and parents in supporting optimal adolescent spiritual growth. AbstrakDukungan iman memiliki peran penting dalam membentuk spiritualitas remaja. Remaja yang menerima dukungan iman secara simultan dari orang tua dan pembina remaja cenderung memiliki tingkat spiritualitas yang lebih tinggi. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan iman orang tua dan dukungan iman pembina remaja terhadap spiritualitas remaja. Penelitian ini menggunakan metode kuantitatif dengan teknik pengumpulan data melalui penyebaran kuesioner. Subjek penelitian terdiri dari 120 remaja berusia 15–25 tahun yang aktif di Gereja Kristen Jakarta. Teknik pengambilan sampel menggunakan purposive sampling, sedangkan analisis data dilakukan dengan uji korelasi Pearson Product Moment. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara dukungan iman orang tua dan dukungan iman pembina remaja terhadap spiritualitas remaja. Dukungan iman yang diberikan secara sinergis oleh kedua pihak menunjukkan korelasi positif yang signifikan terhadap perkembangan spiritualitas remaja. Temuan ini memberikan kontribusi penting dalam pembinaan remaja, dengan menekankan perlunya kolaborasi antara pembina remaja di gereja dan orang tua dalam mendukung pertumbuhan spiritualitas remaja secara optimal.